CULPABILIDAD Y RESPONSABILIDAD PERSONAL EN LAS SANCIONES ADMINISTRATIVAS EN MATERIA DE DEFENSA DE LA COMPETENCIA EN EL DERECHO EUROPEO Y ESPAÑOL - Laguna de Paz, José Carlos (Revista de Derecho, 2019)
The imposition of administrative sanctions for breach of competition law mustrespect the principles of personal responsibility and culpability. In this sense, it isrequired that the action has been autonomously decided by the company. For thesame reason, the principle of legitimate expectations can exclude liability. The directresponsibility of the companies is complemented by the responsibility of themanagers. Spanish legislation affirms the principle of joint and several liabilityin cases of multiple authorship. Breaches of competition law by companies formingpart of a group can be attributed to the parent company, unless its subsidiaryacted autonomously. Responsibility is not always extinguished in case of businessand organizational changes and companies succession.
Keywords: Administrative sanctions; competition law; culpability; personal responsibility; corporate group